Dabrafenib plus trametinib versus dabrafenib monotherapy in patients with metastatic BRAF V600E/K-mutant melanoma: long-term survival and safety analysis of a phase 3 study - Long, Georgina; Utikal, Jochen (Annals of oncology, 2017)
Background: Previous analysis of COMBI-d (NCT01584648) demonstrated improved progression-free survival (PFS) and overall survival (OS) with combination dabrafenib and trametinib versus dabrafenib monotherapy in BRAF V600E/K-mutant metastatic melanoma. This study was continued to assess 3-year landmark efficacy and safety after ≥36-month follow-up for all living patients. Patients and methods: This double-blind, phase 3 study enrolled previously untreated patients with BRAF V600E/K-mutant unresectable stage IIIC or stage IV melanoma. Patients were randomized to receive dabrafenib (150 mg twice daily) plus trametinib (2 mg once daily) or dabrafenib plus placebo. The primary endpoint was PFS; secondary endpoints were OS, overall response, duration of response, safety, and pharmacokinetics. Results: Between 4 May and 30 November 2012, a total of 423 of 947 screened patients were randomly assigned to receive dabrafenib plus trametinib (n = 211) or dabrafenib monotherapy (n = 212). At data cut-off (15 February 2016), outcomes remained superior with the combination: 3-year PFS was 22% with dabrafenib plus trametinib versus 12% with monotherapy, and 3-year OS was 44% versus 32%, respectively. Twenty-five patients receiving monotherapy crossed over to combination therapy, with continued follow-up under the monotherapy arm (per intent-to-treat principle). Of combination-arm patients alive at 3 years, 58% remained on dabrafenib plus trametinib. Three-year OS with the combination reached 62% in the most favourable subgroup (normal lactate dehydrogenase and <3 organ sites with metastasis) versus only 25% in the unfavourable subgroup (elevated lactate dehydrogenase). The dabrafenib plus trametinib safety profile was consistent with previous clinical trial observations, and no new safety signals were detected with long-term use. Conclusions: These data demonstrate that durable (≥3 years) survival is achievable with dabrafenib plus trametinib in patients with BRAF V600-mutant metastatic melanoma and support long-term first-line use of the combination in this setting.